PENGEMBANGAN BAHAN AJAR MENULIS CERITA FIKSI BERBASIS KEUNGGULAN LOKAL UNTUK SISWA SEKOLAH DASAR - Musriah (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
Writing fiction is one of the basic competences of writing skill contained in curriculum 2013 for elementary level. Analysis result found that in the fourth grade material of theme 4 about various work in teaching materials have not shown local advantage in student area. Educators should be able to develop teaching materials that are able to overcome the limitations of fictional story-writing books adapted to local excellence. The development of teaching materials for fiction-based stories of local excellence using Research and Development (R & D) models is able to produce a fictional resource based on local excellence that is eï¬€ectively used as a resource development book.